Means to an end: mechanisms of alternative polyadenylation of messenger RNA precursors. (14th November 2013) - Gruber, Andreas R.; Martin, Georges; Keller, Walter; Zavolan, Mihaela
<x xml:space="preserve">Abstract</x> Expression of mature messenger RNAs (mRNAs) requires appropriate transcription initiation and termination, as well as pre‐mRNA processing by capping, splicing, cleavage, and polyadenylation. A core 3′‐end processing complex carries out the cleavage and polyadenylation reactions, but many proteins have been implicated in the selection of polyadenylation sites among the multiple alternatives that eukaryotic genes typically have. In recent years, high‐throughput approaches to map both the 3′‐end processing sites as well as the binding sites of proteins that are involved in the selection of cleavage sites and in the processing reactions have been developed. Here, we review these approaches as well as the insights into the mechanisms of polyadenylation that emerged from genome‐wide studies of polyadenylation across a range of cell types and states. WIREs RNA 2014, 5:183–196. doi: 10.1002/wrna.1206 Conflict of interest: The authors have declared no conflicts of interest for this article. For further resources related to this article, please visit the WIREs website.